Gadobutrol in Renally Impaired Patients: Results of the GRIP Study. Issue 1 (January 2017) - Michaely, Henrik J.; Aschauer, Manuela; Deutschmann, Hannes; Bongartz, Georg; Gutberlet, Matthias; Woitek, Ramona; Ertl-Wagner, Birgit; Kucharczyk, Walter; Hammerstingl, Renate; De Cobelli, Francesco; Rosenberg, Martin; Balzer, Thomas; et al.
Abstract : Objective: The aim of this study was to assess the potential risk of gadobutrol-enhanced magnetic resonance imaging (MRI) in patients with moderate to severe renal impairment for the development of nephrogenic systemic fibrosis (NSF). Materials and Methods: We performed a prospective, international, multicenter, open-label study in 55 centers. Patients with moderate to severe renal impairment scheduled for any gadobutrol-enhanced MRI were included. All patients received a single intravenous bolus injection of gadobutrol at a dose of 0.1 mmol/kg body weight. The primary target variable was the number of patients who develop NSF within a 2-year follow-up period. Results: A total of 908 patients were enrolled, including 586 with moderate and 284 with severe renal impairment who are at highest risk for developing NSF. The mean time since renal disease diagnosis was 1.83 and 5.49 years in the moderate and severe renal impairment cohort, respectively. Overall, 184 patients (20.3%) underwent further contrast-enhanced MRI with other gadolinium-based contrast agents within the 2-year follow-up. No patient developed symptoms conclusive of NSF. Conclusions: No safety concerns with gadobutrol in patients with moderate to severe renal impairment were identified. There were no NSF cases.